Characteristics and particularities of bacterial community variation in the offshore shellfish farming waters of the North Yellow Sea - Gao, Lei; Yu, Zichao; Liu, Chao; Kong, Ning; Wang, Lingling; Song, Linsheng (Frontiers in Marine Science, 2022)
Bacteria in coastal waters drive global biogeochemical cycling and are strongly related to coastal environmental safety. The bacterial community in offshore shellfish farming waters of North China has its own characteristics and particularities, while the knowledge is limited. In this study, the bacterial community characteristics, the particularities of bacterial community in the waters with surface cold patches (SCPs) and the variation of pathogenic bacteria were investigated in the offshore shellfish farming waters in the North Yellow Sea (NYS) from 2017 to 2019. For all studied samples, Desulfobacterales acted as the keystone species taxon in microbial co-occurrence networks, and the proportional abundance of Actinobacteriota was found to be as low as 1.3%. The abundance of Marinobacter and Synechococcus was remarkably prominent in 13 genera with nitrogen-transforming function. The top two different bacterial functions in the spatial analysis (between the waters with SCPs and the ambient waters) were xenobiotics biodegradation and metabolism and metabolism of cofactors and vitamins, which were same with that in the seasonal analysis (between spring and summer). The abundance differences of most pathogenic bacteria analyzed in this study (11 out of 12 genera) also had the same variation dynamics between the spatial analysis and the seasonal analysis. An ANN predictive model for Vibrio abundance was constructed for Vibrio forecasting, with acceptable predictive accuracy. According to the above results, the bacterial community in the shellfish aquaculture waters in this study was characterized by the enhancing ability of nitrogen removal. Temperature was concluded as the predominant environmental factor to drive the variation of bacterial community function and pathogenic bacteria patterns in the offshore shellfish farming waters with SCPs. The results of this study will further our understanding of the bacterial community characteristics in offshore shellfish farming waters, and help for Vibrio forecasting and coastal environmental safety in aquaculture seawater.